2016
DOI: 10.2337/db16-0522
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Suggests LAMB3 as a Susceptibility Gene for Morbid Obesity

Abstract: Identification of rare sequencing variants with a larger functional impact has the potential to highlight new pathways contributing to obesity. Using whole-exome sequencing followed by genotyping, we have identified a low-frequency coding variant rs2076349 (V527M) in the laminin subunit β3 (LAMB3) gene showing strong association with morbid obesity and thereby risk of type 2 diabetes. We exome-sequenced 200 morbidly obese subjects and 100 control subjects with pooled DNA samples. After several filtering steps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…hASCs were reverse transfected 24 h before induction of adipogenesis using ON-TARGETplus SMARTpool siRNAs targeting SCAMP3 or nontargeting siRNA control #1 (Dharmacon) as previously described 33 . The RNA and medium were collected at days 2, 6 and 9 after the induction of differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…hASCs were reverse transfected 24 h before induction of adipogenesis using ON-TARGETplus SMARTpool siRNAs targeting SCAMP3 or nontargeting siRNA control #1 (Dharmacon) as previously described 33 . The RNA and medium were collected at days 2, 6 and 9 after the induction of differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured until day 7 or 12 of differentiation, at which time the medium and RNA were collected. hMSCs were also reverse transfected 24 h before induction of adipogenesis using ON-TARGETplus SMARTpool siRNAs targeting FAM13A or non-targeting siRNA pool (Dharmacon) as previously described [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…WES of pooled DNA from 100 individuals with morbid obesity and 100 controls of Swedish ancestry followed by targeted genotyping in up to 3,197 case–control subjects identified a low‐frequency variant (rs62623713) in the synaptophysin like 2 ( SYPL2 ) gene associated with morbid obesity and BMI . A similar study in the same population identified a low‐frequency variant (rs2076349) in the laminin subunit beta 3 ( LAMB3 ) gene associated with morbid obesity and BMI . A whole‐exome single‐variant association analysis in 1,205 Hispanic Americans (78 families) identified a low‐frequency variant (rs11554137) in the isocitrate dehydrogenase 1 ( IDH1 ) gene associated with BMI at the conventional genome‐wide level of significance .…”
Section: Established Strategiesmentioning
confidence: 96%